Procesos de Consulta Transparentes: la Construcción del Acuerdo en Las Flores, Mecatlán, Veracruz (Transparent consultation processes: Building agreements in Las Flores, Mecatlán, Veracruz) - Naayeli E. Ramírez-Espinosa; Antonino Santiago Isidro (Oñati Socio-Legal Series)
The regulatory and political system of the Totonac community of Las Flores in the municipality of Mecatlán, state of Veracruz in Mexico is governed by several principles, some of which are the principle of obedience to community agreements, the principle of a transparent life, and the principle of sharing. In this paper the authors discuss these principles and the rules that relate to them in the context of the duty to consult indigenous peoples in Mexico and the relevance of establishing agreements with the Totonac people of Las Flores. This article has as ultimate aim to collaborate in the implementation of agreements between this locality and the different levels of normative creation for the definition of the future and evolution of law in this region.